Incidence and potential risk factors for remdesivir-associated bradycardia in hospitalized patients with COVID-19: A retrospective cohort study - Alsowaida, Yazed Saleh; Shehadeh, Fadi; Kalligeros, Markos; Mylonakis, Eleftherios (Frontiers in Pharmacology, 2023)
Background: Remdesivir is widely used for the management of COVID-19 and several studies have reported bradycardia as a potential side effect associated with this agent. The aim of the present study was to evaluate the incidence rate, severity, and potential risk factors of remdesivir-associated bradycardia. Methods: We performed a retrospective cohort study among hospitalized adult patients with COVID-19 who were treated with remdesivir from March 2020 to October 2021. Our primary outcome of interest was the incidence rate and severity of bradycardia after remdesivir administration. We defined mild bradycardia as a heart rate of 51-59 beats per minute, moderate bradycardia as a heart rate of 41-50 beats per minute, and severe bradycardia as a heart rate of ≤ 40 beats per minute. We also performed univariable and multivariable regression analyses to determine potential bradycardia risk factors. Baseline characteristics were reported as means with standard deviations or medians with interquartile ranges (IQRs). All the statistical tests are shown as odds ratios (ORs) with 95% confidence intervals (CIs). Results: In total, 1,635 patients were included in this study. The median age with IQR was 68 (57-79) years and 51.7% of the patients were male. In total, 606 (37.1%) patients developed bradycardia. Among them, 437 patients (26.7%) developed mild bradycardia, 158 patients (9.7%) moderate bradycardia, while 11 patients (0.7%) experienced severe bradycardia. In our adjusted multivariate logistic regression, the odds of bradycardia development after remdesivir administration were higher among patients with age ≥65 years (OR 1.76, 95% CI: 1.04-2.99, p = 0.04), and those with hypertension (OR 1.37, 95% CI: 1.07-1.75, p = 0.01), and obesity (OR 1.32, 95% CI: 1.02-1.68, p = 0.03). Conclusion: More than 1 out of 3 patients (37%) who received remdesivir for COVID-19 developed bradycardia with the majority of these patients developing mild or moderate bradycardia that is usually a benign manifestation not needing treatment in most cases. Age ≥ 65 years, hypertension, and obesity were potential risk factors for remdesivir-associated bradycardia among hospitalized COVID-19 patients. Clinicians should be aware of this adverse event and consider close clinical monitoring for patients at high risk for this adverse event.